The Leadership Strategies in Addressing Maritime Border Threats to Enhance Surveillance in Indonesian Waters: English - Anwar, Muhamad Faisal; Brigjen TNI Dr. Mitro Prihantoro, S.A.P., M.SC.; Kolonel Laut (K/W) Dr. Deni Setiawati, Ns., M.Kep., MARS. (International Journal of Education, Vocational and Social Science, 2025)
Indonesia, as the world’s largest archipelagic nation, faces significant challenges in maintaining the security of its vast and complex maritime borders. Threats such as illegal fishing, smuggling, piracy, terrorism, and territorial disputes demand adaptive and visionary leadership strategies. This study aims to analyze how the application of strategic leadership can strengthen surveillance systems and safeguard Indonesia’s maritime sovereignty. Theoretical approaches employed include visionary, transactional, and situational leadership models, each contributing to enhancing maritime organizational effectiveness amid evolving threats. The findings indicate that the integration of modern technologies—such as satellites, drones, and radar systems—along with human resource capacity building and cross-sectoral cooperation among the Navy, Coast Guard, Marine Police, and intelligence agencies, plays a crucial role in reinforcing maritime border security. Furthermore, active maritime diplomacy through ASEAN and international cooperation enhances Indonesia’s position in addressing transnational threats. With adaptive, collaborative, and technology-oriented leadership, Indonesia can improve maritime surveillance effectiveness, protect natural resources, and ensure stability and sovereignty across its maritime border regions.